Canine tonsillar neoplasia and tonsillar metastasis from various primary neoplasms. (18th May 2020) - Mickelson, Megan A.; Regan, Daniel; Randall, Elissa K.; Worley, Deanna; Seguin, Bernard
Abstract: Tonsillar metastasis from distant primary tumours has not been described in dogs, and reports are rare in humans. The aims of this study were to determine whether tumour metastasis occurs to the canine palatine tonsils and evaluate whether afferent lymphatics drain to the palatine tonsils via skull indirect computed tomography lymphangiography (ICTL). Retrospective review of the diagnostic laboratory tonsillar histopathology submissions was performed. ICTL studies (n = 53) were retrospectively reviewed by a single radiologist. Of 882 total tonsil histopathology samples, 492 (56%) were considered neoplastic, with 8% of them benign. Of the primary malignant neoplasms of the tonsil, squamous cell carcinoma (55%), lymphoma (17%) and melanoma (12%) were most common. Tonsillar metastasis was confirmed in 41 cases; histopathologic evaluation revealed melanoma (25), carcinoma (10), hemangiosarcoma (2) and one each of fibrosarcoma, malignant histiocytosis, basal cell tumour and undifferentiated sarcoma. A total of 53 tonsillar melanoma cases were identified, of which 25 represented metastasis from a known distant primary tumour and 28 were solely tonsillar, with 9 of these cases having concurrent lymph node metastasis. No ICTL cases had lymphatic contrast drainage to the palatine tonsil. The palatine tonsil is an important site of metastasis for a variety of primary tumour types from many locations. ICTL did not reveal lymphatics draining to the palatine tonsil, which is highly supportive of hematogenous route of metastasis to the tonsil. Tonsillar metastasis may be more common than previously thought. It is recommended to perform a thorough oral examination, including the tonsils, for all oral tumours and melanoma cases.